Anita Desai: Women and Ecology: Exploring the Evolution of Women's Portrayal in Indian Literature (Journal of Advances and Scholarly Researches in Allied Education, 2014)
The portrayal of women in literature is pretty much as old as literature itself. Nonetheless, this portrayal has got ocean changes with regards to appearance of women writers in literary field. These women writers have adopted another strategy in their treatment of women and the issues related with them. Women have been portrayed in different tones and shades since days of yore In the Indian male centric arrangement male strength has frequently given women a secondary status and has left them vulnerable. An investigation of Indian history and society focuses at the presence of many disdainful practices like youngster marriage, polygamy, share framework, upheld widowhood and so on that significantly subvert a woman's presence as human being.